Building Financial Performance Industry Automotive Through Digital Human Resource Management and Learning Agility: The Mediating Role of Employee Resilience - Abdilah; Sopian (Global Research Collaboration, 2026)
The automotive industry confronts escalating challenges due to the intricate repercussions of accelerated digital transformation, evolving technologies, and the dynamics of demanding worldwide rivalry. This necessitates organizations to enhance financial performance sustainably. In this context, management sources such as Power Man Digital and the capacity for adaptive learning are crucial factors in establishing a competitive advantage for organizations. This research aims to analyze the impact of Digital Human Resource Management (DHRM) and Learning Agility on Financial Performance, both directly and indirectly through Employee Resilience as a mediating variable in the automotive industry. This study employs a quantitative technique with an explanatory design. Data was gathered using a distributed questionnaire administered to employees and supervisors within the automobile industry. The sampling technique employed was purposive sampling, while data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to examine inter-variable relationships and mediation effects. Research results indicate a pattern of linkage between factors that is not entirely consistent. Digital Human Resource Management does not significantly impact employee resilience; yet, it still exerts a direct influence on financial performance. Learning agility is demonstrably significant in enhancing employee resilience and financial success, making it the most dominant variable. Employee resilience does not significantly impact financial performance. Furthermore, the mediation analysis indicates that employee resilience does not mediate the relationship between Digital Human Resource Management, Learning Agility, and financial performance. This study concludes that the introduction of digital-based practice management resources, supported by advanced learning capabilities, can enhance staff resilience in the face of change, hence positively impacting the financial performance of the organization. The findings enhance the literature on the digital transformation of HR and offer practical implications for the automobile sector in developing an adaptive, resilient, and innovation-oriented HR management approach that fosters sustainable organizations.